2023
DOI: 10.3390/vetsci10080505
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Retrospective Laboratory Data on the Burden of Bacterial Pathogens Isolated at the National Veterinary Research Institute Nigeria, 2018–2021

Dennis Kabantiyok,
Moses D. Gyang,
Godwin O. Agada
et al.

Abstract: Farm animals harbour bacterial pathogens, which are often viewed as important indicators of animal health and determinants of food safety. To better understand the prevalence and inform treatment, we audited laboratory data at the Bacteriology Laboratory of the NVRI from 2018–2021. Antibiotics were classified into seven basic classes: quinolones, tetracyclines, beta-lactams, aminoglycosides, macrolides, nitrofuran, and cephalosporins. Trends were analysed using a generalised linear model with a log link functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…A study by Enany et al (2019) showed the connection between the frequent use of antibiotics in farm production and treatment and the emergence of multidrug resistance in different bacterial pathogens. Similarly, other studies have emphasized the rising trend in AMR and MDR in low-and middle-income countries such as Nigeria (Osman et al, 2018;Kabantiyok et al, 2023).…”
Section: Discussionmentioning
confidence: 85%
“…A study by Enany et al (2019) showed the connection between the frequent use of antibiotics in farm production and treatment and the emergence of multidrug resistance in different bacterial pathogens. Similarly, other studies have emphasized the rising trend in AMR and MDR in low-and middle-income countries such as Nigeria (Osman et al, 2018;Kabantiyok et al, 2023).…”
Section: Discussionmentioning
confidence: 85%
“…A study by Enany et al (2019) showed the connection between the frequent use of antibiotics in farm production and treatment and the emergence of multidrug resistance in different bacterial pathogens. Similarly, other studies have emphasized the rising trend in AMR and MDR in low-and middle-income countries such as Nigeria (Osman et al, 2018;Kabantiyok et al, 2023).…”
Section: Discussionmentioning
confidence: 85%